2017
DOI: 10.7554/elife.24394
|View full text |Cite
|
Sign up to set email alerts
|

The comprehensive connectome of a neural substrate for ‘ON’ motion detection in Drosophila

Abstract: Analysing computations in neural circuits often uses simplified models because the actual neuronal implementation is not known. For example, a problem in vision, how the eye detects image motion, has long been analysed using Hassenstein-Reichardt (HR) detector or Barlow-Levick (BL) models. These both simulate motion detection well, but the exact neuronal circuits undertaking these tasks remain elusive. We reconstructed a comprehensive connectome of the circuits of Drosophila‘s motion-sensing T4 cells using a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
292
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(311 citation statements)
references
References 46 publications
17
292
1
1
Order By: Relevance
“…Most strikingly, we found that the Mi9 neuron possessed a 5–10° receptive field responsive to OFF-contrast bars (Figure 3D), consistent with prior measurements showing that Mi9 is OFF-contrast selective [22, 28]. Since previous studies have proposed that Mi9 is glutamatergic [26, 28], we expressed the glutamate indicator iGluSnFR [39] in T4 and T5 to measure glutamate release onto T4 or T5 dendrites in response to full field changes in contrast (Figure S3). T5 dendrites lacked glutamate signals in response to full field changes in contrast, consistent with receiving cholinergic inputs (Figure S3) [37].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Most strikingly, we found that the Mi9 neuron possessed a 5–10° receptive field responsive to OFF-contrast bars (Figure 3D), consistent with prior measurements showing that Mi9 is OFF-contrast selective [22, 28]. Since previous studies have proposed that Mi9 is glutamatergic [26, 28], we expressed the glutamate indicator iGluSnFR [39] in T4 and T5 to measure glutamate release onto T4 or T5 dendrites in response to full field changes in contrast (Figure S3). T5 dendrites lacked glutamate signals in response to full field changes in contrast, consistent with receiving cholinergic inputs (Figure S3) [37].…”
Section: Resultssupporting
confidence: 90%
“…For instance, OFF-contrast information could be conveyed by linear ON-cells, or through ON-center cells with surround inhibition. Since the neurons that provide input to T4 are well established [2628], we measured the response properties of four of T4’s major synaptic inputs to discern how OFF-contrast information could reach T4 (Figure 3C). Before mapping their receptive fields with static, 5° bars, we confirmed that they were responsive to stimuli on the screen by measuring their responses to moving 10° bars (see STAR Methods).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that we were recording from the same neuron across animals. In Drosophila , the properties of two types of wide-field excitatory medullary neurons have been recently described: the Lawf2 neurons provide suppressive feedback to large monopolar cells in the lamina [40] and the Tm9 neurons are required for directional motion detection in a broad range of conditions [41]; one recently identified wide-field inhibitory neuron (CT1) has been proposed to modulate the gain of motion detecting T4 cells [42]. Some wide-field inhibitory lobula plate tangential cell (LPTC) characterized in the blowfly, both spiking and non-spiking, such as Vi, VCH and DCH are sensitive to optic flow, but little is known about how their time-varying output influences downstream neurons [4345].…”
Section: Discussionmentioning
confidence: 99%
“…The Drosophila visual system is well suited for genetic manipulation because of the availability of powerful genetic tools, such as an exhaustive collection of cell‐specific Gal4 lines (Jenett et al, ), eye‐specific mosaic analysis (Newsome, Åsling, & Dickson, ) and RNAi lines for almost all Drosophila genes. Recently, analysis using electron microscopy was carried out to reconstruct a connectome, further elucidating the connections in the visual neuronal network (Takemura et al, , ). Additionally, an extracellular interactome of Drosophila membrane and secreted proteins was created (Özkan et al, ).…”
Section: Introductionmentioning
confidence: 99%